Sensitive skin can be small fibre neuropathy: results from a case–control quantitative sensory testing study. (16th September 2018) - Huet, F.; Dion, A.; Batardière, A.; Nedelec, A.S.; Le Caër, F.; Bourgeois, P.; Brenaut, E.; Misery, L.
Summary: Background: Sensitive skin syndrome (SSS) is defined as the occurrence of unpleasant sensations (itch, pain, burning, prickling) in response to stimuli that should not normally cause such sensations. Previous studies show that SSS could be a small fibre neuropathy, but quantitative sensory testing (QST) is lacking. Objectives: Using QST, to determine the presence or absence of tactile sensitivity disorder, mainly heat pain threshold (HPT), in patients with SSS. Methods: This monocentric case–control study included 21 patients with SSS and 21 controls. The patients underwent QST. Neuropathic pain was assessed by two questionnaires: the Douleur Neuropathique 4 (DN4) and the Neuropathic Pain Symptom Inventory (NPSI). Results: Forty‐two patients were included in the study. The HPT was significantly lower in the cases (14·5 ± 2·8) than in the controls (17·8 ± 2·5) ( P < 0·001). Intermediate pain (HPT 5·0) was also significantly decreased in patients with SSS. The DN4 and NPSI scores were significantly higher in the cases than in the controls. Conclusions: The decrease in HPT in patients with SSS compared with controls suggests the presence of hyperalgesia, probably due to the damage of C‐fibres. These findings, as well as the increased DN4 and NPSI scores, strengthen the neuronal hypothesis of SSS and are new arguments for consideration of SSS as small fibre neuropathy. Abstract : What's already known about this topic? Sensitive skin syndrome (SSS) is a frequent condition whose physiopathology remains unclear. What does this study add? Scores of neuropathic pain were significantly higher in patients with SSS than in controls. Heat pain thresholds measured by quantitative sensory testing were significantly decreased, strongly suggesting damage to unmyelinated C‐fibres. These results are new arguments linking SSS to the spectrum of small fibre neuropathy. The management of SSS should be dramatically revised at least for the more severe cases. Respond to this article Plain language summary available online